Mode of Action of Pulegone on the Urinary Bladder of F344 Rats - Da Rocha, Mitscheli S. [UNESP]; Dodmane, Puttappa R.; Arnold, Lora L.; Pennington, Karen L.; Anwar, Muhammad M.; Adams, Bret R.; Taylor, Sean V.; Wermes, Clint; Adams, Timothy B.; Cohen, Samuel Monroe [UNESP] (Oxford University Press, 2012)
Essential oils from mint plants, including peppermint and pennyroyal oils, are used at low levels as flavoring agents in various foods and beverages. Pulegone is a component of these oils. In a 2-year bioassay, oral administration of pulegone slightly increased the urothelial tumor incidence in female rats. We hypothesized that its mode of action (MOA) involved urothelial cytotoxicity and increased cell proliferation, ultimately leading to tumors. Pulegone was administered by gavage at 0, 75, or 150 mg/kg body weight to female rats for 4 and 6 weeks. Fresh void urine and 18-h urine were collected for crystal and metabolite analyses. Urinary bladders were evaluated by light microscopy and scanning electron microscopy (SEM) and bromodeoxyuridine (BrdU) labeling index. Pulegone and its metabolites, piperitenone, piperitone, menthofuran, and menthone, were tested for cytotoxicity in rat (MYP3) and human (1T1) urothelial cells by the 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay. No abnormal urinary crystals were observed by light microscopy. Urine samples (18-h) showed the presence of pulegone, piperitone, piperitenone, and menthofuran in both treated groups. By SEM, bladders from treated rats showed superficial necrosis and exfoliation. There was a significant increase in the BrdU labeling index in the high-dose group. In vitro studies indicated that pulegone and its metabolites, especially piperitenone, are excreted and concentrated in the urine at cytotoxic levels when pulegone is administered at high doses to female rats. The present study supports the hypothesis that cytotoxicity followed by regenerative cell proliferation is the MOA for pulegone-induced urothelial tumors in female rats.
Keywords: pulegone; cytotoxicity; urinary bladder; mode of action; cell proliferation; metabolites